1 ≤ x , y , z ≤ 1 0 0 ∑ max ( x , y , z ) + min ( x , y , z ) = ? The sum is over ordered triples of integers ( x , y , z ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let med ( x , y , z ) stand for the median of the three numbers. Then max ( x , y , z ) + min ( x , y , z ) = ( x + y + z ) − med ( x , y , z ) . Now 1 ≤ x , y , z ≤ n ∑ x = n 2 1 ≤ x ≤ n ∑ x = 2 1 n 3 ( n + 1 ) , and likewise for y , z ; so that 1 ≤ x , y , z ≤ n ∑ ( x + y + z ) = 2 3 n 3 ( n + 1 ) . Now for the sum of the medians. We can pair each triple ( x , y , z ) with ( n + 1 − x , n + 1 − y , n + 1 − z ) ; if the median of the first triple is a , then that of the second triple is n + 1 − a . On average, then, each half of the pair contributes 2 1 ( n + 1 ) to the sum. (If n is odd, the triple ( 2 1 ( n + 1 ) , 2 1 ( n + 1 ) , 2 1 ( n + 1 ) ) remains unpaired, but this does not change our argument.) Therefore 1 ≤ x , y , z ≤ n ∑ med ( x , y , z ) = 1 ≤ x , y , z ≤ n ∑ 2 1 ( n + 1 ) = 2 1 n 3 ( n + 1 ) . Finally, ∑ max ( x , y , z ) + min ( x , y , z ) = ∑ ( x + y + z ) − ∑ med ( x , y , z ) = 2 3 n 3 ( n + 1 ) − 2 1 n 3 ( n + 1 ) = n 3 ( n + 1 ) . With n = 1 0 0 we find the answer 1 0 1 0 0 0 0 0 0 .
Problem Loading...
Note Loading...
Set Loading...
I did it the way you did an earlier problem.
Let's assume 1 ≤ x , y , z ≤ 1 0 0 throughout, so that there are 1 0 0 3 = 1 0 0 0 0 0 0 summands. Now ∑ max ( x , y , z ) + ∑ min ( x , y , z ) = ∑ max ( x , y , z ) + ∑ ( 1 0 1 − max ( 1 0 1 − x , 1 0 1 − y , 1 0 1 − z ) ) = ∑ max ( x , y , z ) + ∑ ( 1 0 1 − max ( x , y , z ) ) = ∑ 1 0 1 = 1 0 1 ( 1 0 0 3 ) = 1 0 1 0 0 0 0 0 0
Small Typo in the problem: They are ordered triples of integers, of course.